Assessment of Oral Hygiene Awareness among College Students in Surat City - Kinner Desai; Sugnesh Patel (Medsci Publications, 2018)
Introduction: The mouth is regarded as the mirror of the body and the gateway to good health. Oral health care for the young adult has potential to contribute to the wellbeing of both child and family. Hence, a survey was carried to know the oral hygiene practice awareness amongst the college students. Methodology: By using a predesigned, pretested semi structured, self administered questionnaire, a survey was conducted among 231 college students. Results: Out of the 231 students, 79.4% were males. Majority (63.6%) of the students cleaned teeth, 105 students always used fluoridated toothpaste, one third have habit of snacking between meals, and 34.6% of the students changed their toothbrushes once in 2 months. 61 students had never visited a dentist in their lifetime. Around 43.7% of the students were thought that poor brushing habit is the reason of tooth decay. Conclusion: Knowledge with respect to oral health among the college students of Surat city is adequate; however, an unhealthy snacking habit, over usage of toothbrushes and practicing tobacco habit show the lack of oral health knowledge in these students.